Hierarchy in Structuring of Resource Selection: Understanding Elk Selection Across Space, Time, and Movement Strategies - Storm Crews; Nathaniel D. Rayl; Mathew W. Alldredge; Eric J. Bergman; Chuck R. Anderson Jr.; Eric H. VanNatta; Joseph D. Holbrook; Guillaume Bastille‐Rousseau (Ecology and Evolution)
ABSTRACT Movement is a fundamental aspect of animal ecology that varies across space, time, and among individuals or groups within a population. Broad‐scale patterns of animal movement are often classified into different movement strategies, such as resident, nomadic, or migratory. While landscape‐level environmental patterns can predict the presence of different movement strategies in an area, elucidating how these patterns downscale to fine‐scale resource selection behaviors remains a challenge. Partially migratory systems, where both migrants and residents coexist, offer a unique opportunity to address these questions. Using tracking data from four Rocky Mountain elk (Cervus canadensis) herds situated primarily within Colorado, USA, we assessed between‐herd, seasonal, and within‐herd variation in resource selection behavior. We modeled fine‐scale seasonal resource selection and compared strategy‐specific behaviors using resource selection functions. Additionally, we used a consistency score to quantify the extent of differentiation in resource selection behavior across strategies, seasons, herds, and groups of covariates. We found variation in strategy frequency within each herd and in selection behavior, highlighting the complexity and context‐dependence of strategy‐specific selection. Despite herd‐specific differences, some consistent trends emerged, with elk avoiding human development and roads at fine scales while selecting areas with higher productivity during summer. Our consistency analysis identified where elk most diverged in their selection behavior, revealing the greatest differences among herds, followed by variation between seasons, and lastly between movement strategies. Elk exhibited more uniform responses to productivity, contrasting with greater differentiation in responses to anthropogenic‐related covariates. Overall, our study improves our understanding of elk behavior across space, time, and movement strategies and sheds light on the hierarchical influences of space and time in constraining behavior.